2009
DOI: 10.1104/pp.109.150128
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging of Cellulose Reorientation during Cell Wall Expansion in Arabidopsis Roots    

Abstract: Cellulose forms the major load-bearing network of the plant cell wall, which simultaneously protects the cell and directs its growth. Although the process of cellulose synthesis has been observed, little is known about the behavior of cellulose in the wall after synthesis. Using Pontamine Fast Scarlet 4B, a dye that fluoresces preferentially in the presence of cellulose and has excitation and emission wavelengths suitable for confocal microscopy, we imaged the architecture and dynamics of cellulose in the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
346
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(379 citation statements)
references
References 35 publications
14
346
4
1
Order By: Relevance
“…In this study, atomic force microscopy was applied to image the primary cell wall from the upper hypocotyls of dark-grown seedlings. It was confirmed by this study that cellulose existed mainly in the form of fibrillar bundles in the cell wall of expanding hypocotyl cells (Anderson et al, 2010;Ding et al, 2014), and the diameter of the fibrillar bundles was in the range of 20 to 150 nm (Fig. 5, B-F), comparable to the size observed in the primary cell wall from maize (Ding and Himmel, 2006).…”
Section: Effects On Cellulose Aggregationsupporting
confidence: 67%
See 3 more Smart Citations
“…In this study, atomic force microscopy was applied to image the primary cell wall from the upper hypocotyls of dark-grown seedlings. It was confirmed by this study that cellulose existed mainly in the form of fibrillar bundles in the cell wall of expanding hypocotyl cells (Anderson et al, 2010;Ding et al, 2014), and the diameter of the fibrillar bundles was in the range of 20 to 150 nm (Fig. 5, B-F), comparable to the size observed in the primary cell wall from maize (Ding and Himmel, 2006).…”
Section: Effects On Cellulose Aggregationsupporting
confidence: 67%
“…5; Anderson et al, 2010;Ding et al, 2014), which might be an important mechanism for the regulation of cellulose-cellulose (Thomas et al, 2013), cellulose-pectin (Wang et al, 2015), and cellulosexyloglucan interactions. It has been observed that ,8% of the cellulose surface is available for cross-bridges with noncellulosic polymers (Bootten et al, 2004;Dick-Pérez et al, 2011).…”
Section: Cellulose Aggregation To Fibrillar Bundlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from being slightly smaller, this mutant has defective root hairs, but it seems clear that Arabidopsis must have alternative ways of regulating the separation of cellulose microfibrils. It is interesting nonetheless that microfibrils seem to be more irregularly spaced in the xyloglucan-deficient mutant (Anderson et al, 2010).…”
mentioning
confidence: 99%